Language, power, and the reproduction of dogmatic ideology in Mihardja’s Atheis: A critical discourse analysis - Andi Farid Baharuddin (LITERA, 2026)
Mihardja’s Atheis was a classic and canonical Indonesian novel. Some previous studies had explored the theological aspect, social criticism, and ideological bias. However, existing literature had yet to examine the power relations and linguistic strategies used to shape the powerless figures’ thoughts: e.g., Hasan, Rukmini, and Kartini. This research filled this gap by investigating how dominant characters employ language to indoctrinate powerless individuals using a Critical Discourse Analysis (CDA). The study addresses two research questions: (a) What language styles, motives, and interests are used by those characters who hold the power in indoctrinating the powerless individuals? and (b) How do powerful characters maintain their power (constructed knowledge) over the powerless individuals? The characters are categorized into two typologies: "the shapers" (the powerful) and "the shaped" (the powerless). Results demonstrate that "the shapers" utilize provocative, persuasive, and figurative language to exert influence. Furthermore, to sustain their constructed knowledge, these dominant figures implement a "stick and carrot" system, utilizing punishment and reward as instruments of control. By focusing on these power relations and language uses in the indoctrinating process, this study provides a new perspective on how linguistic structures function as tools of psychological and social domination within the novel.